2008
DOI: 10.1007/s12253-008-9047-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Examination of Gastrin, Gastrin Precursors, and Gastrin/CCK-2 Receptor in Human Esophageal Squamous Cell Carcinomas

Abstract: A promoting effect of gastrin on stimulating Barrett's oesophagus proliferation has been demonstrated, but whether it plays a regulating role for esophageal squamous cell carcinoma (ESCC) to date has not been fully investigated. The aim of this study is to examine the expressions of gastrin, gastrin precursors and gastrin/CCK-2 receptor in ESCC. Tissue specimen sections from 38 patients with ESSC obtained from a high incidence area of north China were assessed using immunohistochemistry for amidated gastrin, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…However, this study did not detect any overarching correlation with patient data. These results are, in fact, consistent with other CCK2R studies, where no significant relationship has been found between CCK2R expression and lymph node involvement, metastatic disease, overall survival, patient age or sex [ 2 , 7 , 9 , 11 , 14 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this study did not detect any overarching correlation with patient data. These results are, in fact, consistent with other CCK2R studies, where no significant relationship has been found between CCK2R expression and lymph node involvement, metastatic disease, overall survival, patient age or sex [ 2 , 7 , 9 , 11 , 14 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Immunohistochemical examination of IDO and tumor-associated lymphocyte expression in the tumor microenvironment Immunohistochemistry (IHC) was performed in 4-μm sections with Vectastatin Elite Universal ABC-HRP kits (Vector Lab., Burlingame, CA, USA) according to the manufacturer's instructions and our published methods [23,24]. Antigen retrieval was achieved by incubating the Number Tumor invasion Lymph node involvement Metastasis TNM stages T1 T2 T3 N0 N1 M0 M1 I II III ESCC 45 1 9 35 35 10 45 0 1 34 10 Table 1 Basic clinicopathological information of ESCC patients Fig.…”
Section: Tissue Specimens From Esccs and Controlsmentioning
confidence: 99%
“…It is therefore possible that many tissues and organs stimulated by pentagastrin are stimulated also by CCK. Consequently, CCK peptides may contribute to the carcinogenesis of esophageal, gastric, colorectal and, for instance, medullary thyroid carcinomas [14,43,45,[76][77][78][79][80]. This hypothesis deserves an evaluation in view of the frequency of pancreatic and gastrointestinal carcinomas.…”
Section: • Cerebral Tumorsmentioning
confidence: 99%